1975
DOI: 10.1007/bf01267849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the inhalation of catalytically active metallic oxide fumes on rabbits

Abstract: SummaryIn our earlier paper, the intravenous injection of Zn O into rabbits, prepared by heating metallic zinc at 1 000 0 C, resulted in rising body temperature of rabbits It is our postulation that the semiconductor shows properties of an oxidative catalyst in the blood, suggesting that the inhalation of catalytically active metallic oxide fumes, a semiconductor, can cause metal fume fever Catalytically active metallic oxide fumes were produced by heating within the proper temperature range and their absorbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…No significant alteration in temperature was evident between groups, likely as a result of the route of exposure [27] or because of anesthesia, which causes hypothermia.…”
Section: Repeated Zinc Instillation Study In Rabbits With Normal Modmentioning
confidence: 74%
“…No significant alteration in temperature was evident between groups, likely as a result of the route of exposure [27] or because of anesthesia, which causes hypothermia.…”
Section: Repeated Zinc Instillation Study In Rabbits With Normal Modmentioning
confidence: 74%
“…60,61 Other researchers have suggested that zinc as well as certain other metals (such as magnesium), by acting as semiconductors, may serve to catalyze cellular responses directly. 62,63 This hypothesis has been supported by preliminary experimental animal studies showing a difference in response associated with zinc oxide fume with and without dopant materials that would modify its semiconducting potential. However, these preliminary experiments measured change in body temperature only and were apparently not pursued further.…”
Section: Mechanisms Of Metal Fume Fevermentioning
confidence: 90%
“…Since the experiments of Lehmann, a variety of hypotheses have been invoked to explain the mechanism of metal fume fever, including theories that zinc may cause cytotoxic protein release, induce immunologic phenomena, or directly catalyze reactions. 6,48,49,[60][61][62][63] Lehmann originally proposed a hypothesis that zinc, through potential cytotoxicity to either the native cells of the respiratory tract or to bacteria colonizing the airways, caused release of "foreign" proteins that were absorbed, inducing a febrile response. 42 This hypothesis later fell into disfavor.…”
Section: Mechanisms Of Metal Fume Fevermentioning
confidence: 99%